INFLATION AND INTEREST RATE WITH EXCHANGE AS INTERVENING VARIABLES : ON STOCK RETURN: Inflation, Interest Rate, Stock Return and Exchange Rate - Novriyani Novriyani (LPPM Press STIE Indragiri Rengat, 2021)
This research aims to find out Interest Rates and Inflation With Exchange Rates As Intervening Variables: Stock Returns. This type of research uses secondary data. The population of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2020. Sampling techniques used purposive sampling. The research population is a company registered with PT. IDX and sample of 8 companies. The data analysis method used is Path Analysis with SPSS. The results explained that inflation has a positive and insignificant effect on stock returns. Interest rates have a positive and insignificant effect on stock returns. Inflation has a positive and significant effect on the exchange rate. Interest rates have a positive and significant effect on the exchange rate. Inflation and return of stocks through exchange rates have a positive and significant effect on the exchange rate. Interest rates and stock returns through exchange rates have a negative and significant effect on the exchange rate. exchange rates have a positive and significant effect on stock returns. Keywords : Inflation, Interest Rate, Stock Return and Exchange Rate